DIBUJOS ANIMADOS EN LA ENSEÑANZA - MARTIN BARRERA PATIÑO; PABLO ALEJANDRO ARAGON (Universidad Distrital Francisco José de Caldas, 2010)
We present some reflections about using cartoons as an innovative tool for teaching science, as well as for contribute in the practice by teacher researchers. This ideas were part of the results obtained in the seminar "Cartoons", offered by the research group "Physics Education", into the "First Festival, Art and Science for convivence" by Maloka in May, 2009. We analyzed the particular case for physics teaching based on cartoons, thinking about what that's means in physics didactic.